PENGARUH PROFITABILITAS TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING DAN PERTUMBUHAN PENJUALAN SEBAGAI VARIABEL ANTESEDEN: Studi Pada Perusahaan Yang Terdaftar Di IDX30 BEI - Jesicha Junia Fredelia; Bambang Mahmudi; Emma Suryani (Jurnal Bina Bangsa Ekonomika, 2023)
This research aims to find out how profitability affects Saihaim's hair with capital structure as an intervening variable and sales growth as an independent variable. The research population includes IDX30 companies that are listed on the Indonesian Stock Exchange for the 2017-2021 year. The sample is taken from as many as 12 companies using the purposive sampling method. The data analysis technique used in this research uses jailural analysis, classical assumption tests and hypothesis testing. Data analysis in this research uses SPSS for windows version 26. The results of this research show that the growth of other sales has a positive and significant effect on Profitability of 2.255, Profitability has a positive and significant effect on Saihaim's hair gain of 3.821, Profitability is not as significant as 4 structural Modifiability has a significant positive effect on water , Capital Structure has no positive and significant impact on Hairgai Saihaim by -0.525 and Profitability has another direct effect on Hairgai Saihaim by 0.562 dain Capital Structure is not an intervening variable paid for companies that are listed in IDX30 BEI Year 2017-2021).